2012
DOI: 10.1111/j.1747-0803.2012.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repeat Sternotomy during Right Ventricular Outflow Tract Reconstruction

Abstract: Objective Right ventricular outflow tract (RVOT) reconstruction necessitates frequent reoperation. To understand the early outcomes, we analyzed our results to provide the intra‐ and postoperative morbidity and mortality. We hypothesized that multiple previous sternotomies do not influence the morbidity, mortality, or survival. Design We performed a retrospective review of patients who underwent reoperative RVOT reconstruction at the University of Rochester Medical Center and SUNY Upstate Medical Center from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…The overall operative complication rate was approximately 14%, even though the patients underwent multiple sternotomies. This rate was not influenced by the type of conduit in place during the redo procedure and this result corroborates with other reports on the fact that, if approached meticulously in specialized centers, repeat sternotomy can be performed with a minor subsequent morbidity and mortality [ 43 , 44 ]. Allografts and xenografts differ in the host immunogenic response, and when implanting a xenograft, one could expect a greater inflammatory reaction.…”
Section: Discussionsupporting
confidence: 89%
“…The overall operative complication rate was approximately 14%, even though the patients underwent multiple sternotomies. This rate was not influenced by the type of conduit in place during the redo procedure and this result corroborates with other reports on the fact that, if approached meticulously in specialized centers, repeat sternotomy can be performed with a minor subsequent morbidity and mortality [ 43 , 44 ]. Allografts and xenografts differ in the host immunogenic response, and when implanting a xenograft, one could expect a greater inflammatory reaction.…”
Section: Discussionsupporting
confidence: 89%
“…Our operative mortality in the RS group compared with the control PS group showed no statistical difference (1 % versus 0.8 % , p = 1.0 ), which was consistent with Morales’ [ 3 ] report that showed RS was not a risk factor of pediatric cardiac operative mortality. The Kirshbom study [ 4 ] reported that mortality was associated with the number of sternotomy procedures, while the Swartz study [ 5 ] reported that increasing number of previous sternotomies does not increase the overall morbidity and mortality in some patients. Our data also showed the mortality was not associated with the number of sternotomy procedures, but we only had 7 s RS patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Consequently, this patient cohort requires multiple reinterventions during their lifetime. 19 Although a plethora of pulmonary valves and valved conduits are available, the search for an ideal conduit is ongoing. 2,[20][21][22] In the late 1960s, Ross and Somerville described RVOT reconstruction for the first time with an aortic homograft.…”
Section: Discussionmentioning
confidence: 99%